Malignant Melanoma in Child with Xeroderma Pigmentosum: A Rare Case - Riezky Januar Pramitha; Sawitri Sawitri (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Xeroderma pigmentosum (XP) is an autosomal recessive genetic disorder characterized by photosensitivity, cutaneous pigmentary changes, and malignant tumor development at an early age. The basic defect underlying the clinical manifestations is nucleotide excision repair defect, leading to defective repair of ultraviolet (UV)-induced DNA. XP patients who are younger than 20 years of age have more than 1000-fold increased risk of developing malignant neoplasms of the skin, which commonly include squamous cell carcinoma, basal cell carcinoma, fibrosarcoma, and malignant melanoma. Malignant melanoma arises in only about 3% of XP patients. Purpose: To report a case of malignant melanoma in a child with XP. Case: A 7-years-old girl presented with multiple hypopigmentation and hyperpigmentation macules since age of two, throughout the body, more on sun-exposed areas. The physical examination showed solitary tumor extensive ulcero- proliferative surface with areas of hemorrhage and blackish pigmentation on the vertex region. Histological examination revealed a feature of nodular malignant melanoma, and the condition became worse after she underwent two cycles of chemotherapy. Discussion: Despite the rare occurrence, the nodular type of malignant melanoma in XP patients is the most aggressive and responsible for the fatal condition. Conclusion: Early detection of XP is necessary due to its fast-growing nature and high metastatic possibility as well as mortality index.